Review of community-based research : Assessing partnership approaches to improve public health - Israel, Barbara A.; Schulz, Amy J.; Parker, Edith A.; Becker, Adam B. (Annual Review of Public Health, 1998)
« Community-based research in public health focuses on social, structural, and physical environmental inequities through active involvement of community members, organizational representatives, and researchers in all aspects of the research process. Partners contribute their expertise to enhance understanding of a given phenomenon and to integrate the knowledge gained with action to benefit the community involved. This review provides a synthesis of key principles of community-based research, examines its place within the context of different scientific paradigms, discusses rationales for its use, and explores major challenges and facilitating factors and their implications for conducting effective community-based research aimed at improving the public's health » [Résumé original]
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; autochtones; groupes communautaires; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques; santé; santé publique; système colonial; systèmes d'oppressions; thématiques

Le regard de l'autre: artistes canadiens blancs -- sujets féminins noirs = Through an-other's eyes : white Canadian artists -- black female subjects - Nelson, Charmaine; Robert McLaughlin Gallery (Robert McLaughlin Gallery, 1998)
Catalogue d'une exposition tenue du 11 février au 11 avril 1999 à la Robert McLaughlin Gallery, Oshawa, Ont., du 18 juin au 15 août 1999 à la Thames Art Gallery, Chatam, Ont., du 11 janvier au 13 février 2000 à la Galerie d'art Leonard et Bina Ellen, Université Concordia, Montréal et du 16 septembre au 19 novembre 2000 à la Art Gallery of Nova Scotia, Halifax, N.-É.
Keywords: afro-féminisme; amériques; approches et analyses; canada; cours; féminisme afroaméricain; har4610; histoire et politique; premier cycle; représentation des femme*; représentation des femmes* racisées; régions géographiques; système colonial; systèmes d'oppressions; thématiques